Chinese Expert Advisory on Percutaneous Pulmonary Artery Denervation for the Treatment of Pulmonary Hypertension - Chinese Society of Cardiology, Chinese Medical Association; Hanjia Gao (Cardiology Discovery)
Abstract. Pulmonary hypertension (PH) is a condition marked by elevated blood pressure in the pulmonary arteries. Advancements have recently been made in understanding PH pathophysiology, methods of diagnosis, risk assessment, and treatment options. Sympathetic nerve activity plays a significant role in the occurrence and development of PH. Percutaneous pulmonary artery denervation (PADN) is a therapeutic approach for PH that targets sympathetic denervation at 3 crucial points in the main pulmonary artery and the orifice of the left pulmonary artery. The Cardiovascular Clinical Research Group and Pulmonary Vascular Disease Group of the Chinese Society of Cardiology have developed an expert advisory aimed at creating standardized treatment protocols for PH using PADN. The advisory covers experimental foundations, evidence from evidence-based medicine, indications for treatment, and detailed procedural steps for PADN.